Performance of biomarkers NF-L, NSE, Tau and GFAP in blood and cerebrospinal fluid in rat for the detection of nervous system injury - Vlasakova, Katerina; Tsuchiya, Takayuki; Garfinkel, Ivy N.; Ruth, Michael P.; Tyszkiewicz, Cheryl; Detwiler, Theodore J.; Somps, Christopher J.; Di Cesare Mannelli, Lorenzo; Glaab, Warren E. (Frontiers in Neuroscience, 2024)
Background Target organ toxicity is often a reason for attritions in nonclinical and clinical drug development. Leveraging emerging safety biomarkers in nonclinical studies provides an opportunity to monitor such toxicities early and efficiently, potentially translating to early clinical trials. As a part of the European Union’s Innovative Medicines Initiative (IMI), two projects have focused on evaluating safety biomarkers of nervous system (NS) toxicity: Translational Safety Biomarker Pipeline (TransBioLine) and Neurotoxicity De-Risking in Preclinical Drug Discovery (NeuroDeRisk). Methods Performance of fluid-based NS injury biomarker candidates neurofilament light chain (NF-L), glial fibrillary acidic protein (GFAP), neuron specific enolase (NSE) and total Tau in plasma and cerebrospinal fluid (CSF) was evaluated in 15 rat in vivo studies. Model nervous system toxicants as well as other compounds were used to evaluate sensitivity and specificity. Histopathologic assessments of nervous tissues and behavioral observations were conducted to detect and characterize NS injuries. Receiver operator characteristic (ROC) curves were generated to compare the relative performance of the biomarkers in their ability to detect NS injury. Results NF-L was the best performer in detecting both peripheral nervous system (PNS) and CNS injury in plasma, (AUC of 0.97–0.99; respectively). In CSF, Tau correlated the best with CNS (AUC 0.97), but not PNS injury. NSE and GFAP were suitable for monitoring CNS injury, but with lesser sensitivity. In summary, NF-L is a sensitive and specific biomarker in rats for detecting compound-induced central and peripheral NS injuries. While NF-L measurement alone cannot inform the site of the injury, addition of biomarkers like Tau and NSE and analysis in both blood and CSF can provide additional information about the origin of the NS injury. Conclusion These results demonstrate the utility of emerging safety biomarkers of drug-induced NS injury in rats and provide additional supporting evidence for biomarker translation across species and potential use in clinical settings to monitor drug-induced NS injury in patients.